Entre Lapinha da Serra e o Mata Capim: fotografia e relações de trocas simbólicas - Alexandre Romariz Sequeira (2010)
This dissertation examines the procedures that involve an experience in which the photograph is used as a means of interaction and symbolic exchanges with persons or groups. This analysis, searches the intricacies of creation, through its conceptual procedures for its insertion/interaction and its constitution as an artistic object.